406‫ﻣﺪى‬‫ﻣﻼ‬ ‫ؤﻣ‬‫ﺔ‬‫ﺻﻴﻎ‬ ‫اﻟﺘﻤﻮﻳﻞ‬ ‫اﻹﺳﻼﻣﻲ‬ ‫ﻟﺨﺼﺎﺋﺺ‬ ‫اﻟﺘﺠﺎرة‬ ‫اﻟﺨﺎرﺟﻴﺔ‬ ‫دراﺳﺔ‬‫ﺣﺎﻟﺔ‬ ‫ﺑﻨﻚ‬ ‫اﻟﺒﺮﻛﺔ‬ ‫اﻟﺠﺰاﺋﺮ‬ ‫‪‬‬ ‫وﻛﺎﻟﺔ‬ ‫ﻗﺴﻨﻄﻴﻨﺔ‬ ‫ﺳﻴﺪي‬ ‫ﻣﺒﺮوك‬ - ﻣﺒﺮوك ‫ﻣﺮا‬‫ﺑ‬‫ﻂ‬‫ ‬ (My University, 2018)
The foreign trade sector has experienced strong growth internationally in in fact it represents almost a quarter of the GDP of countries today, hence the problem that poses is that of its financing, especially if the operators cannot self-finance, hence the orientation towards external financing, that as a result Islamic financing appeared as a alternative for financing foreign trade especially since it has proven itself, hence the interest of experts in it which makes it as an option for operators in the field of foreign trade. In this context which came our study and which aims to know the compatibility of the formulas of Islamic financing with the specificities of foreign trade. And for this we did our practical study at the level of the Baraka Bank Algeria agency Constantine 406 which is located in Sidi Mabrouk, based on the analysis of documents provided by this and meetings with agency officials. This study demonstrated that in terms of formality the bank has succeeded in adapting the formulas of Islamic financing to the needs of foreign trade, but in substance there is a great difference with traditional financing due to the fact that the latter is only a simple intermediary in the operation against usurious remuneration, but in Islamic financing the bank becomes a major player in the operation by applying the principle of no profit without silk risk grain and loss especially with the MOUSAWAMA formula.